When brightness counts: the neuronal correlate of numerical-luminance interference. - Cohen Kadosh, R; Cohen Kadosh, K; Henik, A (2008)
Previous studies showed that the processing of numerical information and spatial information such as physical size causes a mutual interference. The neuronal correlate of such interference was suggested to be in the parietal lobe. However, a previous study showed that such interference does not occur between numerical information and nonspatial dimensions such as luminance level (Pinel P, Piazza M, Le Bihan D, Dehaene S. 2004. Distributed and overlapping cerebral representations of number, size, and luminance during comparative judgments. Neuron. 41:983-993). Here it is shown that numerical value and luminance level do cause a behavioral interference and that this interference modulates the activity in the parietal lobe. The current results support the idea that the parietal lobe might be equipped with neuronal substrates for magnitude processing even for nonspatial dimensions.